Correction to: The Strengths and Difficulties Questionnaire (SDQ) in Africa: a scoping review of its application and validation - Nikhat Hoosen; Eugene Lee Davids; Petrus J. de Vries; Maylene Shung-King (BMC, 2018)
Abstract After publication of the article [1], it has been brought to our attention that the authors listed in Table 1 are in the wrong order. They should be listed as follows: